Photocatalytic member and method for producing photocatalytic member

JP2025036359APending Publication Date: 2025-03-14DEXERIALS CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024148221
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2024-08-30
Publication Date
2025-03-14

Smart Images

  • Figure 2025036359000001_ABST
    Figure 2025036359000001_ABST
Patent Text Reader

Abstract

To provide a photocatalyst with high productivity for industrial use.SOLUTION: A photocatalytic member comprises, in sequence, a substrate, a base layer, and a photocatalyst layer formed in contact with the base layer, wherein the base layer is composed of a composite oxide of cerium and zinc, and the photocatalyst layer comprises titanium oxide.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photocatalytic member and a method for manufacturing a photocatalytic member. [Background technology]

[0002] Photocatalysts, which are activated by light such as ultraviolet light or visible light, are currently attracting attention due to their various effects. Some of the effects of photocatalysis are particularly known to be the generation of hydrogen / oxygen by photolysis of water, as seen in the Honda-Fujishima effect, strong oxidizing properties due to the generation of active oxygen on the surface, and superhydrophilicity due to the generation of numerous hydroxyl groups on the surface. Photocatalysts can be used in a variety of applications, including sterilizing viruses and pathogens such as the coronavirus, which has been particularly prevalent in recent years, by irradiating them with light, breaking down formaldehyde, which causes sick house syndrome, and forming anti-fogging films using superhydrophilic properties.

[0003] In addition, when photocatalysts are applied to anti-reflective coatings, they are expected to be effective in decomposing fingerprint marks on the surface of the anti-reflective coating. In particular, anti-reflective coatings made of dielectric multilayer films, which are made by alternately laminating inorganic materials with different refractive indices and have a thickness of 1 μm or less, use the interference of light, so even if a small amount of transparent foreign matter such as a fingerprint mark adheres to the surface, the interference effect is lost and the transparent foreign matter is easily visible. Conventionally, anti-reflective coatings have been covered with substances with low surface energy, such as fluorine compounds, to prevent the adhesion of transparent foreign matter such as fingerprint marks, but this was not effective enough and cleaning such as wiping was also required. If transparent foreign matter, which is an organic substance, could be decomposed by photocatalysts, cleaning would no longer be necessary, and photocatalysts are highly anticipated to address this issue.

[0004] Titanium oxide is known as a material with photocatalytic properties. Vacuum thin film formation methods such as sputtering are known as a method for forming titanium oxide on the surface of some substrate. However, in order for titanium oxide to exhibit photocatalytic properties, it needs to be crystallized into anatase or rutile form, and for this to occur, heat treatment at 300°C or higher is required during or after film formation. For this reason, it is difficult to apply photocatalysis to components such as plastics that have low heat resistance. Another method that has been proposed is to apply crystallized titanium oxide fine powder to a substrate together with a binder to fix it. This application method is very widely used because it does not require processing such as heating and allows large-area treatment, and most of the photocatalysts currently on the market are made using this application method. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2007-308729 A [Patent Document 2] JP 2007-314835 A [Patent Document 3] Patent No. 5217023 [Patent Document 4] JP 2000-345320 A [Patent Document 5] Patent No. 4460537 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the binder used to fix the substrate is often an organic substance, and when it comes into contact with the photocatalyst, it decomposes, a phenomenon known as chalking, and the photocatalyst itself falls off. In addition, if the ratio of the binder is increased to strengthen the bond between the substrate and the photocatalyst, the ratio of the photocatalyst decreases relatively, resulting in a decrease in catalytic performance.

[0007] For this reason, it is desirable to form a titanium oxide thin film using a vacuum thin film formation method that does not contain a binder, but the challenge is how to achieve photocatalytic performance when the film is formed at room temperature.

[0008] As a method for obtaining titanium oxide crystallized at room temperature, Patent Document 1 discloses a method in which a single cathode or dual cathode is used and the duty ratio of voltage application is set to a certain value or less. Patent Document 1 describes that crystallized titanium oxide can be obtained by this method, but when the inventors performed a reproduction experiment, they were unable to confirm crystallization, and it is possible that the method depends on the configuration of the equipment.

[0009] In addition, Patent Documents 2 and 3 disclose a method for promoting crystallization by performing the deposition of a titanium metal film and the oxidation treatment separately. However, this requires a complex equipment configuration, and is difficult to realize with a general-purpose sputtering device.

[0010] As an example of using a general-purpose sputtering device, as shown in Patent Document 4, a method has been attempted in which water is added during film formation and heat treatment is performed at a relatively low temperature (200°C or higher) to crystallize the film. However, even though it is low-temperature crystallization, heating at 200°C or higher is required, which causes deformation of many plastic substrates. This results in a problem of lack of versatility.

[0011] As a method for obtaining photocatalytic performance by film formation at room temperature using a general-purpose sputtering device, there is a method for forming a film of zirconium oxide (zirconia) as an underlayer and then forming a film of titanium oxide, as shown in Patent Document 5. This method is an excellent method for realizing photocatalytic performance without subjecting titanium oxide to heat treatment.

[0012] However, since the degree of crystallization of zirconium oxide is low, a certain degree of film thickness is required for the layer to function satisfactorily as an undercoat layer, resulting in low productivity. Furthermore, since zirconium oxide itself is insulating, in order to form a film by sputtering, a technique such as radio frequency (RF) sputtering must be used, but the slow film formation speed and difficulty in achieving a large area result in extremely low productivity. As another method for obtaining photocatalytic performance without a high temperature environment, a method of forming zirconium oxide by direct current reactive sputtering of metallic zirconium in an inert gas and reactive gas environment is also considered. However, since the sputtering conditions change significantly depending on the surface oxidation state of the zirconium oxide target, it is extremely difficult to achieve stable production. The present invention has been made to solve these problems, and its object is to explore an underlayer other than zirconium oxide and to provide a photocatalyst with high industrial productivity. [Means for solving the problem]

[0013] The present inventors conducted extensive research into these issues and arrived at the present invention. They found that by using a composite oxide target made by mixing and sintering cerium oxide (CeO2) and zinc oxide (ZnO) to give the target electrical conductivity, and then forming a film as a base layer by sputtering using this target, and then forming a film of titanium oxide, the titanium oxide of the resulting photocatalytic member exhibits photocatalytic performance without heat treatment.

[0014] Furthermore, they discovered that it is possible to perform DC sputtering by using a target made by mixing and molding cerium oxide (CeO2) and zinc oxide (ZnO) in a substance amount ratio (molar ratio) in the range of 3:1 to 3:2, and that by using this target to form a base layer and then forming a titanium oxide layer without heating, it is possible to produce a photocatalytic component that exhibits particularly good photocatalytic performance.

[0015] The underlayer is preferably a composite oxide of cerium and zinc, but may contain other elements. For example, gallium (Ga) element, aluminum (Al) element, etc. may be contained in order to increase the electrical conductivity of zinc oxide. Furthermore, electrical conductivity is merely necessary for direct current (DC) sputtering, and the underlayer may not be electrically conductive. It is known that the photocatalytic layer obtained with a thickness of 10 nm has the effect of exhibiting photocatalytic performance, but in the case of plastic films, etc., it is desirable for the underlayer to be 20 nm or more in order to ensure the smoothness of the surface. Although a thickness of 20 nm or more can maintain sufficient crystallinity, forming a film with a thickness of 100 nm or more not only places a thermal load on the substrate, but is also industrially inefficient, so the thickness is desirably 100 nm or less.

[0016] The photocatalyst layer in the photocatalyst member of the present invention has titanium oxide (TiO2) as a main component, but may contain other elements as long as the photocatalytic performance is expressed. For example, titanium oxide has a band gap in the ultraviolet region and requires ultraviolet light to operate as a photocatalyst, but there are examples in which nitrogen has been added to make it responsive to visible light. In the present invention, nitrogen can also be added to make it a visible-responsive photocatalyst. In addition, a metal element, for example, niobium, may be added to increase the electrical conductivity of the photocatalyst layer. In addition, in the present invention, titanium oxide does not need to exhibit crystallinity. The thickness of the photocatalyst layer is sufficient as long as it is thick enough to exhibit photocatalytic performance, and may be, for example, 40 nm or more. In addition, the effect of the present invention is shown even if the photocatalyst layer is thick, but it is preferable for the thickness to be 200 nm or less in industrial terms.

[0017] Furthermore, there may be a layer other than the underlayer and the photocatalyst layer on the substrate. For example, a silicon oxide film may be formed on the surface of the photocatalyst layer in order to maintain the superhydrophilicity of the photocatalyst. Also, as seen in the Honda-Fujishima effect, a conductive layer may be formed on the substrate before forming the underlayer in order to use the present invention as a photocatalyst electrode. In either case, the present invention is completed by forming a film of titanium oxide on the surface of the undercoat layer made of a composite oxide of cerium oxide and zinc oxide, the surface being opposite to the substrate.

[0018] That is, the present invention provides the following means. (1) A photocatalytic member according to one embodiment of the present invention is a photocatalytic member comprising, in this order, a substrate, a base layer, and a photocatalytic layer formed in contact with the base layer, wherein the base layer is a composite oxide of cerium and zinc, and the photocatalytic layer contains titanium oxide.

[0019] (2) In the photocatalytic member of (1) above, the mass ratio of cerium oxide and zinc oxide contained in the underlayer may be within a range of 3:1 to 1:1.

[0020] (3) In the photocatalytic member of (1) or (2) above, the element ratio of elements other than titanium oxide contained in the photocatalytic layer may be 10% or less.

[0021] (4) In the photocatalytic member according to any one of the above (1) to (3), the underlayer may have a thickness of 10 nm or more.

[0022] (5) In the photocatalytic members according to any one of (1) to (4) above, the photocatalytic layer may have a thickness of 40 nm or more.

[0023] (6) The photocatalytic members of any of (1) to (5) above may further include a hydrophilicity retaining layer on the photocatalytic layer, and the hydrophilicity retaining layer may contain silicon oxide or a complex oxide of silicon and another metal.

[0024] (7) In the photocatalytic members according to any one of (1) to (6) above, the substrate may be a transparent substrate.

[0025] (8) In the photocatalytic members described above in (1) to (7), the substrate may be a polymer film.

[0026] (9) In the photocatalytic members according to any one of (1) to (8) above, the underlayer may further contain a group III element, and the total amount of the group III element contained in the underlayer may be 10% or less in terms of substance amount ratio.

[0027] (10) A method for manufacturing a photocatalytic member according to one embodiment of the present invention includes a base layer formation step of forming a base layer on a substrate, and a photocatalytic layer formation step of forming a photocatalytic layer containing titanium oxide on the base layer, in which the base layer formation step involves sputtering the substrate using a composite target containing a mixture of cerium oxide and zinc oxide.

[0028] (11) In the method for producing a photocatalytic member according to (10) above, the mixture ratio of cerium oxide and zinc oxide in the composite target may be within the range of 3:1 to 3:2 in terms of substance amount ratio.

[0029] (12) In the method for producing a photocatalyst member according to (10) or (11) above, the composite target may be electrically conductive.

[0030] (13) In the above methods for producing a photocatalytic member according to (10) to (12), the underlayer forming step may involve DC discharge sputtering or AC discharge sputtering.

[0031] (14) In the method for producing a photocatalyst member according to any one of (10) to (13), in the photocatalyst layer forming step, the photocatalyst layer may be formed by sputtering using a target containing any one of titanium, a titanium alloy, and oxygen-deficient titanium oxide.

[0032] (15) In any of the methods for producing a photocatalyst member according to any of (10) to (14) above, the substrate may be a polymer film. Effect of the Invention

[0033] According to the present invention, it is possible to provide a photocatalyst with high industrial productivity. For example, it is possible to provide a photocatalyst member that exhibits photocatalytic performance without high-temperature heat treatment, and a method for producing a photocatalyst member that can use a substrate with low heat resistance, can increase the film formation speed, and can produce a photocatalyst member that exhibits photocatalytic performance. [Brief description of the drawings]

[0034] [Figure 1] 1 is a cross-sectional view showing an example of the configuration of a photocatalytic member according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing the configuration of a photocatalytic member according to a modified example of FIG. [Diagram 3] 2 is a graph showing an XRD spectrum of an underlayer formed on an alkali-free glass substrate in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] The drawings used in the following description may show characteristic parts enlarged for convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto, and can be appropriately modified and implemented within the range in which the effects of the present invention are exhibited. In addition, the upper and / or lower limit values ​​of the numerical ranges described in this specification can be arbitrarily combined to define a preferred range. For example, the upper and lower limit values ​​of the numerical ranges can be arbitrarily combined to define a preferred range.

[0036] [Photocatalytic materials] Fig. 1 is a cross-sectional view showing an example of the configuration of a photocatalyst member according to one embodiment of the present invention. The photocatalyst member 1 shown in Fig. 1 includes, in this order, a base material 2, an underlayer 3, and a photocatalyst layer 4 formed in contact with the underlayer 3, the underlayer 3 being made of a composite oxide of cerium and zinc, and the photocatalyst layer 4 containing titanium oxide. In this embodiment, the number of underlayers 3 and the number of photocatalyst layers 4 are typically one each, and in the example shown in Fig. 1, the photocatalyst layer 4 is the outermost layer of the laminate.

[0037] <Base material> The substrate 2 may be made of any material. Examples of materials for the substrate 2 include glass, metal, resin, and ceramics. Resins that can be used for the substrate 2 include resin films such as polymer films. In particular, resin films with thin resin thickness have many advantages, such as being lightweight and being able to be attached to various locations. Furthermore, for industrial reasons, there is an advantage that film formation can be performed continuously using a roll-to-roll sputtering device for mass production. Furthermore, when used in locations where light transmission is required, such as window glass and displays, a transparent resin (polymer) film may be used.

[0038] The material for the transparent resin film is not particularly limited, but examples that can be used include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyaramid, polyimide, polycarbonate, polyethylene, polypropylene, triacetyl cellulose (TAC), polycycloolefin (COC, COP), etc.

[0039] The substrate 2 is preferably a transparent substrate. The transparent substrate may be made of a transparent material that can transmit light in the visible light range. The transmittance of the transparent substrate for light in the visible light range is, for example, 80% or more.

[0040] The thickness of the substrate 2 is not particularly limited, but when the substrate 2 is a resin film, it is preferable to set the thickness to 20 μm or more and 200 μm or less, taking into consideration ease of handling during manufacturing and thinning of the member. From the viewpoint of improving the scratch resistance of the substrate 2, a coating of, for example, an acrylic resin may be formed on at least one surface of the substrate 2 by, for example, solution coating. In addition, the acrylic resin may have organic or inorganic particles dispersed therein in order to improve the haze and film running properties.

[0041] <Underlayer> The underlayer 3 is a composite oxide of cerium and zinc. The content of cerium and zinc in the underlayer 3 is, for example, in the range of Ce (cerium):Zn (zinc) = 9:1 to 1:1 in terms of the substance ratio. That is, the content of cerium and zinc in the underlayer 3 is, for example, in the range of Ce:Zn = 9:1 or more and 1:1 or less in terms of the substance ratio. The content of cerium and zinc in the underlayer 3 is, for example, in the range of Ce:Zn = 3:1 to 13:12 in terms of the substance ratio, preferably, in the range of 3:1 to 1:1, may be in the range of 3:1 to 1:1, may be in the range of 7:3 to 3:2, may be in the range of 2:1 to 3:2, or may be in the range of 62:38 to 52:48. When the substance ratio of cerium and zinc in the underlayer 3 is in this range, the photocatalytic layer 4 formed directly thereon exhibits particularly good photocatalytic performance.

[0042] The underlayer 3 is preferably made of a composite oxide containing only cerium and zinc as metal elements. That is, the underlayer 3 preferably contains 0% of a third element, which will be described later. On the other hand, the underlayer 3 may contain one or more other elements in addition to cerium, zinc, and oxygen. In this embodiment, a metal element other than cerium and zinc contained in the underlayer 3 is referred to as a third element. The third element is, for example, a gallium (Ga) element, an aluminum (Al) element, or an indium (In) element, which is added to increase the electrical conductivity of zinc oxide. Thus, the third element is, for example, a group III element. The content of the third element other than cerium, zinc, and oxygen in the underlayer 3 is preferably 10% or less. The composition of the underlayer 3 corresponds to the composition of a composite target used in the manufacturing process, which will be described later. The elements contained in the underlayer 3 can be measured, for example, by an X-ray microanalyzer (XMA) or X-ray photoelectron spectroscopy (ESCA). By this measurement, it is also possible to measure the substance amount ratio of the above-mentioned cerium and zinc contents. In the underlayer 3, the total amount of third elements other than cerium and zinc is, for example, in element ratio (substance amount ratio) 10% or less, preferably 5% or less, and more preferably 2% or less. The total amount of the third elements may be 0, or may be 0.5% or more, or 1% or more.

[0043] The resistance value of the target used to form underlayer 3 is preferably 100 Ω cm or less, and more preferably 1 Ω cm or less, when DC sputtering is performed in the manufacturing process. In this embodiment, when direct current (DC) sputtering is performed in the manufacturing process, the target material needs to be conductive, but underlayer 3 formed by sputtering it does not need to be conductive.

[0044] The thickness of the underlayer 3 is, for example, 8 nm or more, preferably 10 nm or more, and more preferably 20 nm or more from the viewpoint of securing a sufficient amount of complex oxide at any point in the in-plane direction because the surface of the substrate 2 may not be smooth when the substrate 2 is a plastic film or the like. In addition, it can be said that sufficient crystallinity can be maintained if the thickness of the underlayer 3 is 20 nm or more. The thickness of the underlayer 3 is preferably 100 nm or less from the viewpoint of suppressing the heat load on the substrate 2 during the manufacturing process and from the viewpoint of saturating the improvement in crystallinity for the photocatalyst layer 4 to exhibit sufficient catalytic performance when the underlayer 3 is sufficiently thick, and the thickness of the underlayer 3 may be 50 nm or less. The thickness of the underlayer 3 can be measured, for example, by preparing a cross-sectional slice of the sample by a microtome method and using a transmission electron microscope.

[0045] <Photocatalyst layer> The photocatalyst layer 4 is a layer that functions as a photocatalyst. The photocatalyst layer 4 contains titanium oxide as a photocatalyst. More specifically, the photocatalyst layer 4 is composed of only titanium oxide, or is composed of titanium oxide and at least one other element with a total titanium element ratio of 10 atomic % or less. Titanium oxide has a band gap in the ultraviolet region, and normally requires ultraviolet light to operate as a photocatalyst, but adding nitrogen makes it responsive to visible light. In the present invention, nitrogen can be added to titanium oxide in the photocatalyst layer 4 to make it a visible-responsive photocatalyst. In this case, the content of nitrogen in the photocatalyst layer 4 is 10 atomic % or less with respect to titanium oxide and titanium element. In addition, a metal element, for example, niobium (Nb), may be included to increase the electrical conductivity of the photocatalyst layer.

[0046] However, this configuration is merely an example, and it is sufficient that the photocatalytic layer 4 contains titanium oxide to an extent that the effects of this embodiment can be obtained. The elements contained in the photocatalytic layer 4 can be measured by, for example, an X-ray microanalyzer (XMA) or an X-ray fluorescence analysis (XRF).

[0047] The thickness of the photocatalyst layer 4 is desirably at least 40 nm or more in order for the photocatalyst layer 4 to function as a photocatalyst. The thicker the photocatalyst layer 4, the better, but since titanium oxide also has a slow film formation speed, it is desirably 200 nm or less from the viewpoint of industrial productivity. The thickness of the photocatalyst layer 4 can be measured, for example, by preparing a cross-sectional slice of a sample by a microtome method and using a transmission electron microscope. Furthermore, in the photodecomposition performance evaluation, even when the thickness of the titanium oxide was increased to a thickness greater than 200 nm, no further improvement in decomposition performance was observed.

[0048] The photocatalytic member according to this embodiment is not limited to the one consisting of a substrate 2, an underlayer 3 and a photocatalytic layer 4 as shown in FIG. 1, and may further have other layers between the substrate 2 and the underlayer 3 or on the photocatalytic layer 4.

[0049] For example, one or more layers of conductive material may be laminated between the substrate 2 and the underlayer 3 in order to provide electrical conductivity to the photocatalyst member 1. Examples of such conductive materials include indium-tin oxide (ITO) and aluminum-zinc oxide (AZO). A metal material may also be laminated. Furthermore, a different oxide may be laminated on the metal material in order to suppress oxidation by plasma when the underlayer 3 is formed. Furthermore, an adhesive layer may be formed in order to ensure adhesion between the substrate 2 and the underlayer 3. Furthermore, when the substrate 2 is a transparent substrate, a transparent material may be formed in order to increase the transparency of the photocatalyst member 1. Furthermore, a smoothing layer may be formed in order to smooth the surface of the substrate 2.

[0050] Also, a transparent material may be formed on the surface of the photocatalyst layer 4. In particular, a hydrophilicity retaining layer containing silicon oxide or a composite oxide of silicon oxide and other metals may be formed on the photocatalyst layer 4 so that superhydrophilicity can be maintained for a long time even in a dark place. FIG. 2 is a cross-sectional view showing the configuration of such a photocatalyst member according to a modified example of FIG. 1. The photocatalyst member 1A shown in FIG. 2 further has a hydrophilicity retaining layer 5 on the photocatalyst layer 4 of the photocatalyst member 1 shown in FIG. 1. When the hydrophilicity retaining layer 5 contains a composite oxide, the metal contained therein is, for example, Na or Al. In addition, since titanium oxide used in the photocatalyst layer is a high refractive index material, a layer of a low refractive index material such as silicon oxide may be laminated on the photocatalyst layer in order to reduce the reflectance of the surface. For example, a low refractive index material layer may be formed in place of the hydrophilicity retaining layer 5 at the position where the hydrophilicity retaining layer 5 is provided in FIG. 2. In addition, a low refractive index material layer may be formed between the photocatalyst layer 4 and the hydrophilicity retaining layer 5.

[0051] [Method of manufacturing photocatalyst member] 1 and 2 can be manufactured, for example, by the method described below. The manufacturing method of the photocatalyst member 1, 1A according to one embodiment of the present invention includes an underlayer forming step of forming an underlayer 3 on the base material 2 and a photocatalyst layer forming step of forming a photocatalyst layer 4 containing titanium oxide on the underlayer 3, and in the underlayer forming step, sputtering is performed on the base material 2 using a composite target in which cerium oxide and zinc oxide are mixed. When manufacturing a photocatalyst member by roll-to-roll, first, the base material 2 wound around an unwinding roll is unwound.

[0052] (Underlying layer formation process) Next, the underlayer 3 is formed on the substrate 2 that has been unwound and appropriately treated. The underlayer 3 may be produced by any method. However, from the viewpoint of stacking different materials to form a multilayer film, the sputtering method is effective. There are various sputtering methods such as radio frequency (RF) sputtering, alternating current discharge (AC) sputtering, and direct current discharge (DC) sputtering, but alternating current (AC) sputtering or direct current (DC) sputtering is mainly used for high-speed, large-area film formation and long-length film formation using a continuous winding device. When radio frequency (RF) sputtering is used, there are almost no restrictions on the target material, and various substances can be sputtered, but as mentioned above, it is not suitable for high-speed, large-area, and long-length film formation. Although alternating current (AC) sputtering or direct current (DC) sputtering requires that the target material used has conductivity, it is suitable for high-speed, large-area, and long-length film formation. The underlayer forming step is performed, for example, in a reduced pressure environment in which a chamber containing the substrate and the composite target is filled with an oxygen and inert gas atmosphere.

[0053] From the viewpoint of producing a photocatalytic member that exhibits photocatalytic performance without high-temperature heat treatment, the underlayer formation step is preferably performed by DC sputtering or AC sputtering among the above methods. When forming the underlayer by DC sputtering or AC sputtering, a conductive composite target is used. In this embodiment, having conductivity means, for example, a resistance of 100 Ω·cm or less. The resistance of the composite target is preferably 100 Ω·cm or less.

[0054] The composite target used in the underlayer forming step is a mixture of cerium oxide and zinc oxide. The composition of the underlayer 3 formed in the underlayer forming step depends on the composition in the composite target. Therefore, by investigating the correlation between the substance ratio of the cerium and zinc contents in the composite target and the substance ratio of the cerium and zinc contents in the underlayer 3 in advance, an underlayer of any composition can be manufactured. That is, in order to form an underlayer having a substance ratio of cerium oxide and zinc oxide within a predetermined range as described above, the substance ratio of cerium and zinc in the composite target is, for example, in the range of Ce (cerium):Zn (zinc) = 9:1 to 1:1, and from the viewpoint of forming a film by DC sputtering, it is preferably in the range of 3:1 to 3:2, more preferably in the range of 18:7 to 13:7, and may be in the range of 7:3 to 13:7. In addition, when forming the underlayer 3 containing a third element other than cerium, zinc, and oxygen, the composite target also contains the corresponding third element. That is, the composite target can contain the same third element as the underlayer 3. For example, the composite target can contain a third element such as gallium, aluminum, or indium, which is added to increase the electrical conductivity of zinc oxide. If the target material does not contain a third element, the composition of the formed underlayer 3 will be almost the same as that of the target material. The third element contributes as a dopant to zinc oxide, lowering the resistance of the target and increasing the deposition rate of the composite target, but it is presumed that a deviation in composition occurs because the rate increase of zinc oxide is greater than the rate increase of cerium oxide.

[0055] The underlayer forming step is carried out, for example, at a pressure (ultimate vacuum) of 10 -2 Sputtering can be performed under conditions of 50 Pa and 10 Pa. The sputtering power can be, for example, 50 to 300 W.

[0056] The composite target used in the underlayer forming step can be prepared, for example, by weighing and mixing the raw material powders, and sintering, powder molding, etc. When preparing a composite target by mixing the raw material powders and then sintering them, the heating temperature can be, for example, 1000 to 1400°C, and the heating time can be, for example, 2 to 6 hours. When preparing a composite target by powder molding, the raw material powders can be placed in a die and pressed with an upper punch and a lower punch to form the composite target.

[0057] (Photocatalyst layer formation process) Next, the photocatalyst layer 4 is formed on the underlayer 3. The photocatalyst layer 4 may be produced by any method. However, from the viewpoint of laminating different materials to form a multilayer film, a sputtering method is effective.

[0058] When forming the photocatalytic layer 4 on the underlayer 3 by sputtering, the target may be, for example, titanium, a titanium alloy, oxygen-deficient titanium oxide, or a composite oxide containing oxygen-deficient titanium oxide. The titanium alloy may contain niobium, copper, tungsten, or the like in addition to titanium element. The oxygen-deficient titanium oxide is a titanium oxide represented by the general formula TiOx, where x is a value less than 2.

[0059] In the photocatalytic layer forming step, for example, oxygen and argon gas are sealed in a chamber accommodating the substrate 2 having the underlayer 3 formed on its surface and the target, and sputtering is performed in a reduced pressure environment.

[0060] According to the manufacturing method of the photocatalyst member and the photocatalyst member of the above embodiment, a photocatalyst with high industrial productivity can be realized by using a composite oxide of cerium and zinc in the underlayer 3. For example, after the photocatalyst layer 4 is formed, the photocatalyst layer 4 can exhibit its photocatalytic function without being heated.

[0061] Cerium oxide and zirconium oxide are insulators. Therefore, while it is possible to form a film using radio frequency (RF) sputtering, it is not possible to form a film using normal direct current (DC) sputtering. Radio frequency sputtering is an excellent method in that it can form a film even on insulators, but the film formation speed is significantly slower than direct current (DC) sputtering. In addition, since it uses the same frequency band as radio waves, leakage during film formation at high power may cause serious radio interference in the surrounding area, and it is not suitable for high-speed and large-area production, which is important for industrial applications. In particular, when using a roll-to-roll film formation method in which the underlayer and photocatalyst layer are formed consecutively on a film, it is considered desirable to form both the underlayer and the photocatalyst layer by sputtering, although it is possible to use deposition methods, etc.

[0062] In the above embodiment, the composite target of cerium oxide and zinc oxide used in forming the composite oxide of cerium and zinc in the underlayer exhibits electrical conductivity that cerium oxide does not exhibit, so that the underlayer can be formed by DC sputtering without RF sputtering.

[0063] Therefore, according to the above embodiment, it is possible to provide a method for producing a photocatalyst member that exhibits photocatalytic performance without high-temperature heat treatment, that can use a substrate with low heat resistance, that can increase the film formation speed, and that can produce a photocatalyst member that exhibits photocatalytic performance. In addition, since the sputtering conditions do not change significantly depending on the surface oxidation state of the target, it is easy to achieve stable production.

[0064] Moreover, in the photocatalyst members 1 and 1A according to the above-described embodiments, it is believed that a crystal lattice is formed by the underlayer 3, and titanium oxide grows in a manner to match the crystallites, thereby exhibiting good photocatalytic performance. In addition, when forming the underlayer 3 by the sol-gel method, it is difficult to uniformly form a thin film of about 100 nm or less, especially on a film, and therefore it is considered difficult to form a photocatalyst layer 4 that exhibits good photocatalytic performance without heating. EXAMPLES

[0065] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0066] [Example 1] First, as a preparation step, cerium oxide (CeO2) powder and gallium-doped zinc oxide (GZO) powder were weighed and mixed in a material ratio of 7:3, and then heated at 1400°C for 4 hours to produce a sintered target for the underlayer (composite target). The resistivity of the composite target thus produced was measured using Loresta GP MCP-T610 (Nitto Seiko Analytech Co., Ltd.).

[0067] Next, non-alkali glass (OA-10G manufactured by Nippon Electric Glass Co., Ltd.) was prepared as the substrate. The substrate was washed with a neutral detergent, then ultrasonically cleaned in pure water for 10 minutes, and after being pulled out of the liquid, the liquid droplets were immediately removed with an air gun and dried. The substrate was set in a four-source sputtering device (manufactured by Toei Scientific Industry Co., Ltd., model number: SPV-420), and after exhausting, a film was formed. The sputtering device used can use both DC discharge and RF discharge by a changeover switch. In Example 1, the undercoat layer formation process was performed by DC discharge.

[0068] Detailed conditions for the underlayer forming step are shown below. (Sputtering conditions) Target dimensions: 2 inch diameter, 4mm thickness Distance between target and substrate: 80mm ·Achieved vacuum level: <1×10 -3 Pa ·Substrate temperature: room temperature Sputtering power: DC 100W

[0069] As described above, the underlayer was formed to a thickness of 50 nm by DC sputtering. Furthermore, titanium oxide (TiO2) was laminated on top of it to a thickness of 150 nm as a photocatalytic layer under the following film-forming conditions, and then the sample was taken out to prepare a sample. The photocatalytic layer was formed using oxygen-deficient titanium oxide TiOx as a target. (Sputtering conditions) Target dimensions: 2 inch diameter, 4mm thickness Distance between target and substrate: 80mm ·Achieved vacuum level: <1×10 -3 Pa ·Substrate temperature: room temperature Sputtering power: RF200W

[0070] [Example 2] In preparing the composite target used in the underlayer formation process, a sample was prepared under the same conditions as in Example 1, except that cerium oxide (CeO2) powder and gallium-doped zinc oxide (GZO) powder were mixed in a substance weight ratio of 3:1.

[0071] [Example 3] In preparing the composite target used in the underlayer formation process, a sample was prepared under the same conditions as in Example 1, except that cerium oxide (CeO2) powder and gallium-doped zinc oxide (GZO) powder were mixed in a substance weight ratio of 3:2.

[0072] [Example 4] A sample was prepared under the same conditions as in Example 1, except that the thickness of the underlayer was 10 nm.

[0073] [Example 5] A sample was prepared under the same conditions as in Example 1, except that the thickness of the photocatalyst layer was 40 nm.

[0074] [Example 6] In preparing the composite target used in the underlayer formation process, a sample was prepared under the same conditions as in Example 1, except that cerium oxide (CeO2) powder and zinc oxide (ZnO) powder were mixed in a substance weight ratio of 7:3.

[0075] [Example 7] In preparing the composite target used in the underlayer formation process, a sample was prepared under the same conditions as in Example 1, except that cerium oxide (CeO2) powder and aluminum-doped zinc oxide (AZO) powder were mixed in a substance ratio of 7:3.

[0076] (Sputtering conditions) Target dimensions: 2 inch diameter, 4mm thickness Distance between target and substrate: 80mm ·Achieved vacuum level: <1×10 -3 Pa ·Substrate temperature: room temperature Sputtering power: RF 200W

[0077] [Comparative Example 1] A sample was prepared by laminating titanium oxide to a thickness of 150 nm as a photocatalytic layer without forming an underlayer. That is, in Comparative Example 1, TiO2 was directly formed as a photocatalytic layer on an alkali-free glass substrate. The layer composed of TiO2 was formed by sputtering using the same target as in Example 1.

[0078] [Comparative Example 2] A sample was prepared under the same conditions as in Example 1, except that oxygen-deficient niobium pentoxide (NbOx) was used as the target for the underlayer.

[0079] [Reference example 1] A target for the underlayer was prepared as a composite target by mixing cerium oxide (CeO2) powder and gallium-doped zinc oxide (GZO) powder in a substance weight ratio of 4:1, and then sintering was performed under the same conditions as in Example 1. When DC sputtering was attempted on an alkali-free glass substrate using this composite target under the same conditions as in Example 1, discharge was not possible in the DC sputtering device, and a sample with an underlayer formed on the substrate could not be prepared.

[0080] [evaluation] The photocatalytic performance of the prepared samples was evaluated in accordance with JIS R 1703-1 (Fine ceramics - Self-cleaning test method for photocatalytic materials - Part 1: Measurement of water contact angle). Specifically, under black light with a radiance of 2.0 mW / cm 2 The sample was placed in a position adjusted to the desired temperature and left to stand for 24 hours or more. Then, oleic acid was added at 100 cm 2 The contact angle at this point was taken as the initial contact angle. After measuring the initial contact angle, the irradiance was increased to 2.0 mW / cm under black light. 2 The sample was left in this position for 24 hours, then taken out and the contact angle was measured again to obtain the contact angle after UV irradiation. According to the photocatalytic performance assessment criteria of the Photocatalysis Industry Association, a contact angle of 30° or less after UV irradiation can be said to have good photocatalytic performance.

[0081] In addition, the thickness of the underlayer of each sample immediately after the underlayer formation process was evaluated using a spectroscopic ellipsometry (M-2000, manufactured by JAWoollam). Ellipsometry provides the amplitude ratio Ψ and phase difference Δ of p-polarized light and s-polarized light for each wavelength, and by applying an appropriate optical model to these and performing fitting including the film thickness as a parameter, the film thickness can be obtained along with the optical constants. The film thickness was determined based on the measurement results at the center of the substrate.

[0082] The sample preparation conditions, the resistivity of the composite target for preparing the underlayer, and the evaluation results regarding the photocatalytic performance are summarized in Table 1. In Table 1, the entry "OK" in the "Discharge" column of the underlayer indicates that discharge was possible using a DC sputtering device under the same sputtering conditions as in Example 1, and the entry "NG" indicates that discharge was not possible. "Infinity" in the target resistance column indicates that the resistance was above the measurement limit.

[0083] [Table 1]

[0084] [Evaluation Results] <Examples 1 to 3> As is clear from Table 1, discharge was possible when the mass ratio of CeO2 to GZO was in the range of 3:1 to 3:2. In addition, when the prepared sample was irradiated with UV light for 24 hours after coating with oleic acid, the contact angle was 30° or less, indicating sufficient self-cleaning performance and good photocatalytic performance. <Example 4> In contrast to Example 1, even when the undercoat layer was formed to a thickness of 10 nm, when oleic acid was applied and then irradiated with UV light for 24 hours, the contact angle was 30° or less, indicating sufficient self-cleaning performance and good photocatalytic performance. <Example 5> In contrast to Example 1, even when the titanium oxide photocatalyst layer was formed to a thickness of 40 nm, when oleic acid was applied and then irradiated with UV light for 24 hours, the contact angle was 30° or less, indicating sufficient self-cleaning performance and good photocatalytic performance. <Example 6> Discharge was possible even when a composite target for the underlayer was prepared using zinc oxide (ZnO) instead of GZO in Example 1. In addition, when oleic acid was applied to the prepared sample and then UV light was irradiated for 24 hours, the contact angle was 30° or less, indicating sufficient self-cleaning performance and good photocatalytic performance. <Example 7> Discharge was possible even when a composite target for the underlayer was prepared using aluminum-doped zinc oxide (AZO) instead of GZO in Example 1. In addition, when oleic acid was applied to the prepared sample and then UV light was irradiated for 24 hours, the contact angle was 30° or less, indicating sufficient self-cleaning performance and good photocatalytic performance.

[0085] <Comparative Examples 1 and 2> When titanium oxide was formed directly on the substrate without forming an underlayer (Comparative Example 1), or when a metal oxide other than a composite oxide of cerium and zinc was formed as an underlayer and titanium oxide was formed on it (Comparative Example 2), the contact angle after 24 hours of irradiation with UV light after application of oleic acid did not become 30° or less, and it was confirmed that the self-cleaning performance was not exhibited and the photocatalytic performance was not possessed. Thus, a titanium oxide layer formed without an underlayer, or a layer other than a composite oxide of cerium and zinc formed as underlayer 3 and a layer formed directly on it do not have photocatalytic performance.

[0086] [Composition of the base layer] In order to investigate the composition of the underlayer, the underlayer was formed under the same conditions as in the examples, reference examples, and comparative examples using each target, and then removed without forming a photocatalytic layer, and the element ratio of Ce and Zn was evaluated by X-ray photoelectron spectroscopy (ESA). The results are shown in Table 1. [Evaluation of crystallinity] In Example 1, the sample immediately after the formation of the underlayer was evaluated by XRD. XRD was performed using X'Pert PRO MPD (manufactured by PANalytical) with Cuα as the radiation source at an incidence angle of 1°. The results of XRD are shown in Figure 3. For comparison, Figure 3 also shows XRD of zinc oxide, cerium oxide, and zirconium oxide. As the XRD spectra of zinc oxide, cerium oxide, and zirconium oxide, the XRD spectra of a 50 nm thick film formed by RF sputtering on the same alkali-free glass substrate as in Example 1 are shown.

[0087] As shown in Figure 3, a cerium oxide peak can be confirmed close to the zirconium oxide peak position, and its narrow half-width suggests the presence of larger crystallites than those of zirconium oxide. This suggests that cerium oxide is easier to crystallize. In contrast, a thin film formed from a composite target of cerium oxide and gallium-doped zinc oxide shows an XRD similar to that of cerium oxide, and the crystallite size is presumed to be about the same as that of cerium oxide. The graph also shows the XRD of zinc oxide, and a comparison of the peak positions suggests that the crystals confirmed in the cerium oxide-gallium-doped zinc oxide are cerium oxide crystallites.

[0088] The reason why the titanium oxide formed on the underlayer formed of a composite oxide of cerium and zinc exhibits photocatalytic performance is thought to be due to partial heteroepitaxial growth. It is thought that the underlayer forms a crystal lattice, and the titanium oxide grows to match the crystallites. Therefore, if the underlayer side is clearly crystallized with a thin film thickness, it is thought that the titanium oxide of the photocatalytic layer formed later will also promote crystallization. [Explanation of symbols]

[0089] 1, 1A: photocatalytic member, 2: substrate, 3: undercoat layer, 4: photocatalytic layer, 5: hydrophilic retaining layer

Claims

1. A photocatalytic member including, in this order, a substrate, a base layer, and a photocatalytic layer formed in contact with the base layer, the underlayer is a composite oxide of cerium and zinc, A photocatalytic member, wherein the photocatalytic layer contains titanium oxide.

2. 2. The photocatalytic member according to claim 1, wherein the mass ratio of cerium oxide and zinc oxide contained in said underlayer is within a range of 3:1 to 1:

1.

3. 2. The photocatalytic member according to claim 1, wherein the element ratio of elements other than titanium oxide contained in said photocatalytic layer is 10% or less.

4. The photocatalytic member according to claim 1 , wherein the thickness of the underlayer is 10 nm or more.

5. The photocatalytic member according to claim 1 , wherein the photocatalytic layer has a thickness of 40 nm or more.

6. A hydrophilic retaining layer is further provided on the photocatalyst layer, The photocatalytic member according to claim 1 , wherein the hydrophilicity retaining layer contains silicon oxide or a complex oxide of silicon and another metal.

7. The photocatalytic member according to claim 1 , wherein the substrate is a transparent substrate.

8. The photocatalytic member according to claim 1 , wherein the substrate is a polymer film.

9. 2. The photocatalytic member according to claim 1, wherein the underlayer further contains a group III element, and the total amount of the group III element contained in the underlayer is 10% or less in terms of substance amount ratio.

10. A base layer forming step of forming a base layer on the substrate; and forming a photocatalyst layer on the underlayer, the photocatalyst layer including titanium oxide being formed on the underlayer. A method for producing a photocatalytic member, wherein in the underlayer forming step, sputtering is performed on the base material using a composite target containing a mixture of cerium oxide and zinc oxide.

11. The method for producing a photocatalytic member according to claim 10, wherein the mixture ratio of cerium oxide and zinc oxide in the composite target is within a range of 3:1 to 3:2 in terms of substance amount ratio.

12. The method for producing a photocatalytic member according to claim 10, wherein the composite target has electrical conductivity.

13. The method for producing a photocatalyst member according to claim 10, wherein in the underlayer forming step, DC discharge sputtering or AC discharge sputtering is performed.

14. 11. The method for producing a photocatalyst member according to claim 10, wherein in the photocatalyst layer forming step, the photocatalyst layer is formed by sputtering using a target containing any one of titanium, a titanium alloy, and oxygen-deficient titanium oxide.

15. The method for producing a photocatalytic member according to claim 10, wherein the substrate is a polymer film.

Citation Information

Patent Citations

  • Electrophotographic developing material and method of forming color electrophotographic image

    JP1977017023A

  • Thin film structural body and its production

    JP2000345320A

  • Method for forming thin film of crystalline titanium dioxide, and photocatalytic thin film

    JP2007308729A

  • Method of manufacturing hydrophilic thin film

    JP2007314835A

  • Photocatalytic material

    JP4460537B2